1996
DOI: 10.3109/00952999609001682
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Cocaine with Alcohol or Cigarettes

Abstract: Cocaine abusers (N = 42) from an inpatient drug rehabilitation program were interviewed regarding combined use of cocaine with alcohol or cigarettes. Concurrent use of alcohol and cocaine was reported by 37 patients and concurrent use of cigarettes and cocaine by 41 patients. All but two concurrent users reported simultaneous use of alcohol or cigarettes with cocaine. Increased cocaine effect was perceived by 43% of simultaneous alcohol users compared with 15% of simultaneous cigarette users. Patients experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Thus, interpretation of our results to the general population of cocainedependent individuals requires caution. Of particular concern with regard to cognitive functioning is the high prevalence of comorbid alcohol dependence among those with cocaine use disorders, which is estimated to be at least 50% (e.g., Higgins, Budney, Bickel, Foerg, & Badger, 1994;Wiseman & McMillan, 1996). It is also well known that the contemporaneous use of alcohol and cocaine results in the formation of cocaethelyene, which has greater than additive immediate effects on psychological and physiological functioning.…”
Section: Limitationsmentioning
confidence: 97%
“…Thus, interpretation of our results to the general population of cocainedependent individuals requires caution. Of particular concern with regard to cognitive functioning is the high prevalence of comorbid alcohol dependence among those with cocaine use disorders, which is estimated to be at least 50% (e.g., Higgins, Budney, Bickel, Foerg, & Badger, 1994;Wiseman & McMillan, 1996). It is also well known that the contemporaneous use of alcohol and cocaine results in the formation of cocaethelyene, which has greater than additive immediate effects on psychological and physiological functioning.…”
Section: Limitationsmentioning
confidence: 97%
“…10 Cigarettes and cocaine are often used in close temporal proximity. 11 Smoked cocaine and cigarettes share common discriminative stimuli (eg, lighters, smoke). Substance-related cues play a critical role in drug use and relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between nicotine and cocaine are of interest because, in addition to the shared dopaminergic mechanism of action, epidemiological studies have shown a strong concordance between tobacco and cocaine abuse (Budney et al, 1993;Roll et al, 1996;Wiseman & McMillan, 1996). For example, smoking is 3.4 times more prevalent in cocaine abusers than in the general population (Budney et al, 1993) and cocaine-dependent individuals who are cigarette smokers report using cocaine more frequently and in greater amounts than those who are not smokers (Roll et al, 1996).…”
Section: Introductionmentioning
confidence: 99%